Individual characteristics, psychosocial factors, and sleep quality with work fatigue among technical service employees in the National Electricity Company, Bantul - Artha, Dian Parama; Surono, Agus; Pribadi, Ari Prayogo (Universitas Gadjah Mada, 2024)
Purpose: This study aims to determine the relationship between individual characteristic factors, psychosocial factors, and sleep quality on work fatigue among Yantek employees at National Electricity Company (PLN), Unit (ULP) Bantul. Methods: The method used in this study is a quantitative method with a cross-sectional design. The population in this study used a total sample of 55. The research instruments used the IFRC, COPSOQ III, and PSQI. Data analysis uses univariate tests, chi-square tests, and field observations. Results: Work fatigue among Yantek employees was categorized as mild in 47.27%, moderate in 40%, and severe in 12.73%. There was a significant relationship between individual characteristics such as age (<0.001), water consumption (0.004), smoking status (0.008), exercise habits (0.005), shift work (0.003), and work duration (<0.001). There was a significant relationship between psychosocial factors and work fatigue in the demand domain in the workplace (0.003), content and job organization (0.003), interpersonal relationships and leadership (0.007), and individual and job interactions (0.003). There was a significant relationship between sleep quality (p = 0.001) and work fatigue. Conclusion: Individual characteristics were associated with work fatigue. Psychosocial factors were associated with work fatigue. Sleep quality also had a significant relationship with work fatigue.